SIKAP DAN PARTISIPASI PETANI DALAM KEGIATAN PENYULUHAN PADI SAWAH DI KELURAHAN LABIBIA KOTA KENDARI - Jamaluddin, Aisyah; Abdullah, Sukmawati; Salahuddin, Salahuddin; Dima, Darsilan (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Agricultural extension has been instrumental in developing agriculture by enhancing the quality of agricultural human resources. This study was conducted on 112 rice paddy farmers in the village of Labibia in December 2022, using simple random sampling. The research sample consisted of 28 farmers from Labibia village. This study examines the variables of extension agents' attitudes, including extension methods, techniques, materials, and media, as well as farmers' participation in activity planning, implementation, and monitoring and evaluation. The logical structure and causal connections between statements are maintained, and the text is free from grammatical errors, spelling mistakes, and punctuation errors. This study examines the variables of extension agents' attitudes, including extension methods, techniques, materials, and media, as well as farmers' participation in activity planning, implementation, and monitoring and evaluation. The text adheres to conventional structure and formatting, including consistent citation and footnote style. No changes in content were made. The data analysis utilized descriptive and rank Spearman correlation analyses. The language used is clear, concise, and objective, with a formal register and precise word choice. The study revealed that farmers in the village of Labibia rated the implementation of agricultural extension activities as 'medium' across four indicators: extension methods, techniques, materials, and media used by extension workers. This means that the implementation of extension activities still needs improvement in four indicators to ensure that farmers can fully benefit from the extension process. In Labibia village, farmers' participation in agricultural extension activities falls under the medium category. The three indicators are activity planning, activity implementation, and monitoring and evaluation of agricultural extension activities. In implementing extension activities, it is necessary to ensure participation between farmers and agricultural extension workers to achieve the planned goal of farmer independence. The attitude and participation of farmers in agricultural extension activities have a strong, unidirectional relationship. This means that the higher the farmers' attitude, the higher their participation in extension activities.